Synthesis of high surface area porous carbon from anaerobic digestate and it's electrochemical study as an electrode material for ultracapacitors (vol 9, pg 36343, 2019) - Chaturvedi, Vikash; Usgaonkar, Saurabh; Shelke, Manjusha V. (RSC Advances, 2020)
Correction for `Synthesis of high surface area porous carbon from anaerobic digestate and it's electrochemical study as an electrode material for ultracapacitors' by Vikash Chaturvedi et al., RSC Adv., 2019, 9, 36343-36350.